Rotulagem de produtos alimentícios voltados para o público infantil: alegações e teor de nutrientes críticos - Alessandro Rangel Carolino Sales Silva (2019)
Consumers find it difficult to properly interpret information conveyed on food labels. Many food products carry positive claims on their front label, in clear and straightforward language, while the content of critical nutrients is omitted. Front-of-package (FOP) labeling models, conveying information on this nutrients (sugar, fats and sodium) has emerged as strategy to better inform consumers about the nutritional composition of ultra-processed products. In this context, the objective was to analyze the labels of eight categories of food intended for children, available on the market, in relation to the presence of nutritional and other claims, and check for simultaneous occurrence of critical nutrient and/or the presence of sweeteners, following the parameters determined by the Pan American Health Organization (PAHO), as well as evaluating the presence of critical nutrients by different nutritional profile proposals. Information was collected from 409 labels (65 fruit drinks, 34 dairy drinks, 103 stuffed cookies, 43 cakes, 30 breakfast cereals, 50 gelatins, 34 yoghurts and 50 corn chips) that contained some appeal aimed at children, in supermarkets located in Belo Horizonte-MG, Brazil. The critical nutrient content (sugars, total fat, saturated fat, trans fat, sodium and presence/absence of sweeteners) was calculated, based on the parameters determined by PAHO and the presence and types of nutritional claims and/or marketing strategies that enhance the product and was highlighted on the front panel of the label were verified. The percentage of products with “high”, “medium” and “low” critical nutrient content according to different nutritional profiles (Associação Brasileira das Indústrias de Alimentos – ABIA, Gerência-Geral de Alimentos less restrictive – GGALI 1 e Gerência-Geral de Alimentos more restrictive – GGALI 2) and the agreement of these profiles with the profile proposed by PAHO (Kappa agreement test) was also calculated. The information about the sugar content of the products was only available on 122 labels. On average, 64.7% of labels have claims enhancing some positive feature of the product. The morning cereals group had the highest percentage of front labels with claims (86.7%), followed by the fruit drinks group (83.1%). It was observed that in three of the eight food groups, all products also had some nutrient in concentration considered critical by PAHO, being the most frequent sodium, sugar and saturated fat. In the remaining five groups, only one product (for stuffed cookies and breakfast cereals) and three products (for cakes and gelatins) had no nutrient evaluated at critical content. Regarding the different models of nutritional profile used, according to the PAHO parameter, 95% of fruit drinks were classified as “high” in sugar, while only 5% according to ABIA and GGALI 1. Analyzing the high sugar content, it was observed that in the model proposed by ABIA, only dairy drinks (100%), filled cookies (5.7%) and fruit drinks (5.0%), would be categorized as “high” in this nutrient, while by PAHO all categories except corn chips, have values above 90% for “high in sugar”. Breakfast cereal, gelatins, yogurt and corn snack categories also do not have any high saturated fat and sodium products, according to parameters proposed by ABIA. The profile that most agrees, significantly, with PAHO was the GGALI 2 (Kappa > 0,621). It was also observed that for the analyzed nutrients, PAHO's model was the one that most highlighted “high content” foods (saturated fat: 48.4%; total fat: 42.8%; sugars: 85.2%; sodium: 27.9%). It was concluded that there is coexistence between the presence of claims that exalt some positive feature of the product with the presence of content considered critical for another nutrient, which can confuse the consumer for the actual nutritional value of the product, especially in foods aimed at the children. Moreover, it was found with the present study that the nutrient profile presented by ABIA was more flexible in the proposed levels for identification of critical nutrients, when compared with the other models, and PAHO’s was the most restrictive.